The rise of the Right : English nationalism and the transformation of working-class politics - Winlow, Simon; Hall, Steve; Treadwell, James (Lecturer in criminology) (Policy Press, 2016)
This book is the first to offer an uncompromising look at the English Defence League (EDL), aiming to alter thinking about working-class politics and the rise of right-wing nationalism in de-industrialised English towns and cities.
Keywords: Nationalism -- England.; Right-wing extremists -- England.; Political activists -- England.; Nationalisme -- Angleterre.; Extrémistes de droite -- Angleterre.; Activistes -- Angleterre.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- Political Process -- Political Parties.; Nationalism; Political activists; Right-wing extremists; England